Non‐pharmacological approaches for treatment of premature ejaculation: a systematic review. Issue 2 (22nd February 2023) - Pizzol, Damiano; López Sánchez, Guillermo F; Ilie, Petre Cristian; Bertoldo, Alessandro; Trott, Mike; Tully, Mark A; Wilson, Jason J; Veronese, Nicola; Soysal, Pinar; Carrie, Anne; Ippoliti, Simona; Pratsides, Luke; et al.
Abstract : Premature ejaculation is a common male condition worldwide with prevalence estimates varying from 30% to 85%. Owing to the lack of a clear definition and a clear understanding of the potentially multifactorial pathophysiology, treatment remains challenging. The aim of this systematic review was to evaluate the non‐pharmacological treatment modalities for PE to inform clinical practice and patients.